Dielectric relaxation dynamics and AC conductivity scaling of metal-organic framework (MOF-5) based polymer electrolyte nanocomposites incorporated with ionic liquid. (25th September 2017) - Dutta, Rituraj; Kumar, A
Abstract: Dielectric relaxation dynamics and AC conductivity scaling of a metal-organic framework (MOF-5) based poly (vinylidene fluoride-co-hexafluoropropylene) (PVdf-HFP) incorporated with 1-Butyl-3-methylimidazolium hexafluorophosphate have been studied over a frequency range of 40 Hz–5 MHz and in the temperature range of 300 K–380 K. High values of dielectric permittivity ( ε ′ ) having strong dispersion are obtained at low frequency because of interfacial polarization. The real part of the dielectric modulus spectra ( M ′) shows no prominent peak, whereas the imaginary part ( M ″) shows certain peaks, with a reduction in relaxation time ( τ ) that can be attributed to a non-Debye relaxation mechanism. The spectra also depict both concentration- and temperature-independent scaling behavior. The power law dependent variation of AC conductivity follows the jump relaxation model and reveals activated ion hopping over diffusion barriers. The value of the frequency exponent is observed to decrease with increasing concentration of ionic liquid, indicating the forward hopping of ions in the relaxation process. The AC conductivity scaling curves at different temperatures also depict the temperature-independent relaxation dynamics.